C-Terminal Ubiquitination of p53 Contributes to Nuclear Export - Lohrum, Marion A. E. (American Society for Microbiology (ASM), 2001)
The growth inhibitory functions of p53 are controlled in unstressed cells by rapid degradation of the p53 protein. One of the principal regulators of p53 stability is MDM2, a RING finger protein that functions as an E3 ligase to ubiquitinate p53. MDM2 promotes p53 nuclear export, and in this study, we show that ubiquitination of the C terminus of p53 by MDM2 contributes to the efficient export of p53 from the nucleus to the cytoplasm. In contrast, MDM2 did not promote nuclear export of the p53-related protein, p73. p53 nuclear export was enhanced by overexpression of the export receptor CRM1, although no significant relocalization of MDM2 was seen in response to CRM1. However, nuclear export driven by CRM1 overexpression did not result in the degradation of p53, and nuclear export was not essential for p53 degradation. These results indicate that MDM2 mediated ubiquitination of p53 contributes to both nuclear export and degradation of p53 but that these activities are not absolutely dependent on each other.